Peripheral mechanism of a carbonyl hydrosilylation catalysed by an SiNSi iron pincer complex. Issue 12 (24th September 2015) - Metsänen, Toni T.; Gallego, Daniel; Szilvási, Tibor; Driess, Matthias; Oestreich, Martin
Abstract : The metal centre remains a spectator through the peripheral mechanism investigated by a combined spectroscopic, crystallographic, and computational analysis. Abstract : Combined experimental and theoretical analysis of the carbonyl hydrosilylation catalysed by an iron(0) pincer complex reveals an unprecedented mechanism of action. The iron(0) complex is in fact a precatalyst that is converted into an iron(ii ) catalyst through oxidative addition of a hydrosilane. Neither the hydrogen atom nor the silicon atom bound to the iron(ii ) centre are subsequently transferred onto the carbonyl acceptor, instead remaining at the sterically inaccessible iron(ii ) atom throughout the catalytic cycle. A series of labelling, crossover and competition experiments as well as the use of a silicon-stereogenic hydrosilane as a stereochemical probe suggest that the iron(ii ) site is not directly involved in the hydrosilylation. Strikingly, it is the silyl ligand attached to the iron(ii ) atom that acts as a Lewis acid for carbonyl activation in this catalysis. The whole catalytic process occurs on the periphery of the transition metal. Computation of the new peripheral as well as plausible alternative inner and outer sphere mechanisms support the experimental findings.